Hungarian Pension System and its Reform - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2009)
The goal of this study is to present an insider view on the pension reforms implemented in Hungary between 1996 and 2009. Both political economy as well as institutional economics will be used as the main approaches to analyse and explain the reform process and some of its effects. The following studies provide valuable insights: Palacios and Rocha (1998), Bokros and Dethier eds. (1998), Augusztinovics (1999), Augusztinovics et al. (2002), Simonovits (1999), (2000), (2008a), Czúcz and Pintér (2002), European Commission (2006), Gál (2006), Impavido and Rocha (2006), and Guardiancich (2008). The structure of the paper is as follows: Section 1 considers the legacy of the pension system. Section 2 summarises the debate on the pension reform and the basic decisions. Section 3 outlines the implementation of the pension reform, while Section 4 discusses the implementation problems. Section 5 describes the changes since the reform, while Section 6 analyses and Section 7 evaluates the reform. An Appendix discusses the issues of contribution rates.
Keywords: H55; J14; J26; J32; 330; Hungary; pension reform; social security; private pension; Altersvorsorge; Rentenreform; Ungarn